Effects of External Stimulators on Engineered Skeletal Muscle Tissue Maturation. Issue 1 (17th November 2020) - Mueller, Claudia; Trujillo‐Miranda, Mairon; Maier, Michael; Heath, Daniel E.; O'Connor, Andrea J.; Salehi, Sahar
Abstract: Engineering functional skeletal muscle tissue is an ongoing challenge because of the complexity of the in vivo microenvironment and the various factors that contribute to the development and maintenance of the native tissue. However, the growing understanding of the natural skeletal muscle's microenvironment in vivo, as well as the ability to successfully reproduce these factors in vitro, are contributing to the formation of engineered skeletal muscle tissues (SMTs) with greater biomimetic structure and function. This review first summarizes the structure of skeletal muscle tissue. The role of various hydrogels, biomaterials, and scaffolds as building blocks of complex skeletal muscle structures is then explored. Additionally, the role of external stimuli and regulators that can be applied during in vitro culture that lead to the formation of SMT models with higher functionality is examined. These include various physical, biochemical, electrical, mechanical, and magnetic stimulations, as well as biological stimulation through coculture with fibroblasts, endothelial, or neuronal cells. Finally, examples of recently developed functional tissue models that have been developed for in vitro and in vivo applications and the future outlook for this field are discussed. Abstract : A wide variety of parameters have been used to engineer skeletal muscle tissue and guide cell behavior and tissue formation, such as different biomaterials, topography, cells and regulators. In this review paper, the focus is on the combination of the aforementioned parameters and their cooperation in the formation of sophisticated skeletal muscle models.